208k views
5 votes
-x + 3 if the x values are -1, 0, 1, and 2

1 Answer

0 votes

Answer:

The values are 4, 3, 2, and 1 respectively.

Explanation:

Let us assume that y = (- x + 3) ......... (1)

We have to find the values of y for different x values and the x values are - 1, 0, 1, and 2.

Now, from equation (1), we get

For x = - 1, y = (- x + 3) = [- (- 1) + 3] = 1 + 3 = 4.

For, x = 0, y = (- x + 3) = 0 + 3 = 3

For, x = 1, y = (- x + 3) = - 1 + 3 = 2 and

For, x = 2, y = (- x + 3) = - 2 + 3 = 1 (Answer)

User Cel Skeggs
by
4.4k points